2021
DOI: 10.1016/j.jbc.2021.100953
|View full text |Cite
|
Sign up to set email alerts
|

Heparin promotes fibrillation of most phenol-soluble modulin virulence peptides from Staphylococcus aureus

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…2b shows the FTIR spectrum of LMWH and OL, it was found that both of them had characteristic absorption peaks at 892 cm −1 and 936 cm −1 . 23,24 The C–O–S stretching vibration absorption peak of the sulfuric acid group on amino hexose appeared around 830 cm −1 , the strong absorption peak of O–S stretching vibration appeared around 1240 cm −1 , and the CO stretching vibration peak of the sulfuric acid group in the carboxyl group appeared around 1621 cm −1 was also found in both, all of these indicated that the main structure of the OL obtained after oxidation did not change significantly. It has been known that the reason for the conspicuous anticoagulant activity and cytocompatibility of LMWH is the presence of a reactive pentose structure in its molecular chain, 25 they can bind to antithrombin III (AT III), change the conformation of the antithrombin molecules, and inhibit the activity of coagulation factors IIa, Xa and IXa, exhibiting strong anticoagulant properties.…”
Section: Resultsmentioning
confidence: 86%
“…2b shows the FTIR spectrum of LMWH and OL, it was found that both of them had characteristic absorption peaks at 892 cm −1 and 936 cm −1 . 23,24 The C–O–S stretching vibration absorption peak of the sulfuric acid group on amino hexose appeared around 830 cm −1 , the strong absorption peak of O–S stretching vibration appeared around 1240 cm −1 , and the CO stretching vibration peak of the sulfuric acid group in the carboxyl group appeared around 1621 cm −1 was also found in both, all of these indicated that the main structure of the OL obtained after oxidation did not change significantly. It has been known that the reason for the conspicuous anticoagulant activity and cytocompatibility of LMWH is the presence of a reactive pentose structure in its molecular chain, 25 they can bind to antithrombin III (AT III), change the conformation of the antithrombin molecules, and inhibit the activity of coagulation factors IIa, Xa and IXa, exhibiting strong anticoagulant properties.…”
Section: Resultsmentioning
confidence: 86%
“…In the case of PSMβ2 heparin is even capable of altering the dominating molecular mechanism of aggregation from primary nucleation and elongation dominated to being dominated by secondary nucleation. 183 …”
Section: Interactions Between Functional Amyloids and Components Pres...mentioning
confidence: 99%
“…In the case of PSMb2 heparin is even capable of altering the dominating molecular mechanism of aggregation from primary nucleation and elongation dominated to being dominated by secondary nucleation. 183 In summary, the formation of functional amyloids in the extracellular environment of the biolm appears to be optimized ensuring that the biomolecules in the biolm are generally benecial for the aggregation process.…”
Section: Interactions Between Functional Amyloids and Other Extracell...mentioning
confidence: 99%
“…The pH modulation of their aggregation mechanisms was recently reported (41) with PSMα1 found to aggregate through a mechanism dominated by secondary nucleation at neutral pH. Other factors also modulate PSM fibrillation, such as the sulfated polysaccharide heparin [ 22 ]. The production of PSMα peptides by S. aureus is stringently regulated and is associated with virulence.…”
Section: Introductionmentioning
confidence: 98%